Ovine androgen receptor exon1 polymorphism - no association with cryptorchidism - KUMAR, G S NAVEEN; NAGARAJA, C S; JAYASHANKAR, M R; NAGARAJA, R (The Indian Journal of Animal Sciences, 2015)
The exon1 of androgen receptor (AR) coding for N-terminal domain (NTD) has 3 regions of CAG and a GGC repetitive sequence coding for glutamine and glycine repeats respectively. The position and number of these trinucleotide repeats varies with the species and said to have evolutionary significance. In humans, shorter CAG repeats and longer GGC repeats are found to be associated with risk of cryptorchidism. The work was taken up to know the status of trinuclotide repeats and polymorphism in exon1 of ovine AR gene and its association with cryptorchidism. Partial sequences covering the repetitive regions of exon1 of ovine AR gene were PCR amplified from genetically unrelated 80 normal and 60 cryptorchid sheep. Single stranded conformation polymorphism and sequencing revealed no polymorphism at any of the 3 CAG sites and a GGC site of exon1 of ovine sequence. The number of trinucleotide repeats in ovine AR gene were 4, 7, 8 and 6 for CAG-I, CAG-II, CAG-III and GGC regions respectively. The 2 novel SNP 362 C>G and 603 C>T with the frequency of 0.03 and 0.27, respectively, in whole population was found unassociated with the cryptorchidism in sheep. Substitution mutation 362 C>G resulting in 121 Alanine>Glycine, was found to be non effective on protein function by SIFT algorithm.